Amalan Terbaik dalam Rekabentuk Aplikasi M-Pembelajaran: Best Practices in the M-Learning Design - Mohamad, Marlina (Online Journal for TVET Practitioners, 2021)
E-learning applications or online learning is a very broad topic. This article discusses best practices in designing online learning to provide the best learning experience to students. Recently too many e-learning applications have been produced to help the learning process to be easily accessible anytime and anywhere. Students are so excited because access to learning materials is no longer limited to printed materials. The results of studies on the effectiveness of online learning show inconsistent findings. This is because most of the applications developed do not emphasize effective design. If applications are developed without considering the design principles of an effective e-learning application, it is impossible to provide a meaningful learning experience to students. So, these best practices have been gathered through analytical documents from books, journal articles and successful e-learning developers to help designers and developers of e-learning applications to produce effective applications. There are three main things that need to be emphasized in the design of e-learning applications, namely interface design, content design and interaction design. In interface design, among the things that are evaluated is how to produce an interface that can use the cognitive load effectively. Meanwhile, for content design, what is the appropriate learning and teaching theory to be applied so that the learning experience becomes something meaningful. For interaction design, it is important for the behavior of an application to be predictable and usable. Good interaction design shows features such as easy to use, efficient, safe, easy to learn and easy to remember how to use it. In this article, best practices for designing according to these three aspects will be discussed. Although these best practices are still not comprehensive, they can help learning application developers, teachers, instructors, lecturers, or trainers to be able to provide online learning materials and design e-learning interesting applications effectively.